Telaah Pemikiran Antropologi Talal Asad Terhadap Konsep Adab Sebagai Bagian Dalam Komunikasi Budaya Islam Lokal Suku Sasak NTB - Hasipa, Muhammad Ikhwan Fiddaraini (Ulul Albab: Journal Da`wah and Social Religiosity, 2025)
This study explores the transformation of linguistic politeness and its influence on local Islamic cultural communication among the Sasak community in Lombok. Using a qualitative ethnographic approach, the research investigates how the concept of adab a moral and spiritual code of conduct manifests through language and behavior. Data collected through participatory observation and in-depth interviews reveal that expressions such as tiang, nggih, nunas ampure, and matur tampiasih, along with greeting and visiting customs (nyapaq and mesilaq), embody the living values of adab lisan or verbal etiquette. These polite linguistic and behavioral forms act as mechanisms for constructing moral and social identity, strengthening the link between Islamic values and local cultural traditions. Interpreted through Talal Asad’s theory of the discursive tradition, the findings indicate that these communicative practices represent a continuity between normative Islamic teachings and lived local expressions. The study highlights how adab serves as a bridge between religion and culture, promoting moral discipline and social harmony. Ultimately, the research contributes to Islamic anthropology by deepening understanding of how language reflects ethical and spiritual dimensions of Islam in local contexts, while encouraging further studies on adab variation across Indonesian communities.